2006
DOI: 10.2340/00015555-0130
|View full text |Cite
|
Sign up to set email alerts
|

Penile Intraepithelial Neoplasia: Results of Photodynamic Therapy

Abstract: Failure of response to treatment or recurrent disease is often noted in patients with penile intraepithelial neoplasia. Photodynamic therapy has recently been added to the list of treatment modalities used for this diagnosis. Our primary objective was to study the results of photodynamic therapy in the treatment of penile intraepithelial neoplasia in men over the age of 40 years. Ten patients aged 42-82 years with histopathologically confirmed lesions were studied. Lesions initially responded to photo-dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 32 publications
(28 reference statements)
0
30
0
Order By: Relevance
“…There was sustained clearance in the remaining patients over 46 months, including clearance of human HPV DNA. 162 In difficult cases, Mohs micrographic surgery has been used to include tissue taken from the distal urethra and the defect covered by a flap repaired from the external part of the prepuce. Total glans surgical resurfacing was reported to be effective in a series of 10 patients, with good cosmesis.…”
Section: Penile Intraepithelial Neoplasiamentioning
confidence: 99%
“…There was sustained clearance in the remaining patients over 46 months, including clearance of human HPV DNA. 162 In difficult cases, Mohs micrographic surgery has been used to include tissue taken from the distal urethra and the defect covered by a flap repaired from the external part of the prepuce. Total glans surgical resurfacing was reported to be effective in a series of 10 patients, with good cosmesis.…”
Section: Penile Intraepithelial Neoplasiamentioning
confidence: 99%
“…The treatments of penile carcinoma were phodynamic therapy, 5-Fluorouracil cream, cryosurgery with liquid nitrogen and Nd-YAG laser therapy. [5][6][7][8] Laser treatment of T1 and T2 stage carcinoma penis has several advantages. During or post laser, there is no blood loss, pain relief is achieved with oral analgesics, there is no wound infection, and antibiotic administration is not required.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with methyl aminolevulinate PDT for carcinoma in situ of the penis, excellent cosmetic results have been reported, but three out of ten patients had histopathologically residual disease (Axcrona et al 2007 ). Also, Paoli et al ( 2006 ) found initially a response to photodynamic therapy in seven out of ten patients treated with delta-5-aminolevulinic acid or methyl aminolevulinate PDT. Four of these patients presented no recurrences during a mean follow-up of 35 months and were completely cleared after two to eight treatments (mean 4.5 treatments).…”
Section: Photodynamic Therapymentioning
confidence: 99%